Palestine-Israel conflict in the perspective of Habermas' public space theory - Al Fauzi, Andika Fariq; Chatlina, Chiara Dewi; Putri, Devina Aulia Surya; Marshanda, Rachma Ayu (Jurnal Penelitian Humaniora, 2024)
The escalating Palestine-Israel conflict has captured global attention, especially within digital public spaces. This study analyzes public communication regarding the conflict through Habermas' public sphere theory, focusing on platform X as a digital discussion arena. The research employs a descriptive qualitative approach, combining literature reviews and online observations on platform X. Findings reveal that platform X serves as a key medium for individuals and institutions to express opinions and share information about the conflict. Dominant hashtags such as #FreePalestine and #FreeGaza reflect widespread global concern. However, platform X imposes content moderation, limiting freedom of expression and indicating a lack of communication democracy in the digital public sphere. This study highlights the importance of fostering inclusive and unrestricted public spaces that align with Habermas' principles of democratic communication.